Does Ramadan fasting influence injury incidence and injury pattern in professional muslim football athletes? - Farooq, A.; Eirale, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Ramadan is the holy month of Islam, during which Muslims observe fasting (i.e. abstaining from eating and drinking) from sunrise to sunset. Among football players, Ramadan fasting is known to influence unhealthy dietary habits and disturbed circadian rhythms. Not being able to rehydrate during daytime in combination with lack of sleep may mediate increased susceptibility to injury during Ramadan. The aim of the present study was to investigate incidence and pattern of football injuries during Ramadan month among Muslim athletes practicing Ramadan fasting. Methods: A total of 462 first division Muslim athletes from Qatar Stars league(QSL) were followed up for their total exposure to match as well as training sessions for three consecutive seasons that included the Ramadan month. All injuries were assessed for type, location, severity, mechanism and pattern by professional medical staff. Injury incidence was calculated as rate per 1000h of game exposure and data was compared between Ramadan and non Ramadan periods. Results: During the three seasons, the football players sustained, on an average 5.0 injuries per 1000 hours of game (95% CI 4.6- 5.3). No differences were seen in injury incidence during Ramadan month (4.0/ 1000h) compared to non Ramadan period (4.9/ 1000h), p=0.266. Most common during Ramadan month were thigh injuries, with an injury rate of 1.4 per 1000 hours, and knee injuries, with a rate of 1.0 per 1000 hours. Muscular strains dominated in Ramadan month, with an injury rate of 1.5 per 1000 hours of activity. However, these patterns and injury severity were found to be similar with rest of the non Ramadan period. Discussion: Ramadan fasting was not associated with increased risk of injury among Muslim athletes observing Ramadan fasting and moreover athletes presented with similar injury patterns as non Ramadan period. This study should be interpreted in light of the fact that at QSL, all training and competitions during Ramadan take place at least 4h after the break of fast. Further studies that that also adjust for training intensity and sleep quality may provide better understanding of injury incidence during Ramadan.